2017
DOI: 10.3168/jds.2017-12872
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified Lactococcus lactis producing a green fluorescent protein–bovine lactoferrin fusion protein suppresses proinflammatory cytokine expression in lipopolysaccharide-stimulated RAW 264.7 cells

Abstract: Lactoferrin (LF), an iron-binding glycoprotein distributed widely in the biological fluids of mammals, is believed to play an important role in host defenses against infection. Previous studies in animal models and humans demonstrated that combined administration of LF and probiotic lactic acid bacteria (LAB) can prevent sepsis. In this study, we genetically engineered a probiotic LAB strain, Lactococcus lactis, to produce recombinant bovine LF based on the green fluorescent protein (GFP)-fused expression syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Lipopolysaccharide (LPS) induces acute inflammation and endotoxic shock in experimental animals [ 3 , 11 , 12 , 13 ], and it is characterized by the production of cytokines and other mediators of inflammation. Therefore, LPS may be used to induce inflammation to evaluate the anti-inflammatory effect of fermented milk.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) induces acute inflammation and endotoxic shock in experimental animals [ 3 , 11 , 12 , 13 ], and it is characterized by the production of cytokines and other mediators of inflammation. Therefore, LPS may be used to induce inflammation to evaluate the anti-inflammatory effect of fermented milk.…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin can also have anti-inflammatory effects and reduce gut permeability. Several other studies also have demonstrated that lactoferrin reduced LPS-induced inflammation via suppression of TLR4/MyD88/NF-kB pathway [126][127][128]. In vitro studies have also demonstrated that bovine lactoferrin can increase the integrity of the epithelial intestinal barrier [129] It has been shown that a population in Okinawa, Japan with healthy plant-based foods has 9% lower risk of COVID-19 infection and 41% lower risk of severe COVID-19 [130,131].…”
Section: Nutraceuticals and Mineralsmentioning
confidence: 98%
“…Therefore, regulatory mechanisms of OCT are urgently needed to improve prognosis of therapy as well as exploration of innovative therapeutic targets for intestinal mucositis. LPS is a virulent component from gram-negative bacteria that can induce excessive immune response through TLR4 [25]. Many TLRs including TLR2, TLR4, TLR5 and TLR9 are involved in intestinal mucositis [26].…”
Section: Discussionmentioning
confidence: 99%